2022
DOI: 10.1111/aswp.12266
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the self‐care practices of social workers in China under the COVID‐19 pandemic

Abstract: The self‐care practices of social workers have garnered increasing attention in the literature, yet little is known about the case of China. To explore the self‐care practices of Chinese social workers under the COVID‐19 pandemic, this study uses the Self‐Care Practice Scale (SCPS) to measure the self‐care practices of social workers (N = 1066) in Fujian Province, China. The results indicate that Chinese social workers engage in moderate amounts of self‐care practices under the COVID‐19 pandemic. Significant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The general public was exposed to fake news [27] and conspiracy theories [28], which generated technostress [29] and multitasking behavior [30]. The lack of clear public policies generated mental distress [31,32] and an urgency for self-care behaviors [33,34] including the use of unproven drugs [25,35,36] and medicinal plants [25,36] in part based on their knowledge and appreciation of plants containing bioactive 2 of 15 compounds [37][38][39][40][41][42][43][44][45][46][47][48]. It has been further reported that this has impacted the vaccination intention [49].…”
Section: Introductionmentioning
confidence: 99%
“…The general public was exposed to fake news [27] and conspiracy theories [28], which generated technostress [29] and multitasking behavior [30]. The lack of clear public policies generated mental distress [31,32] and an urgency for self-care behaviors [33,34] including the use of unproven drugs [25,35,36] and medicinal plants [25,36] in part based on their knowledge and appreciation of plants containing bioactive 2 of 15 compounds [37][38][39][40][41][42][43][44][45][46][47][48]. It has been further reported that this has impacted the vaccination intention [49].…”
Section: Introductionmentioning
confidence: 99%